Educational Values According to Basic Dramas Structure in Childrens Theatre - Razaw Rasheed Sabri; Ibrahim Qader Mohammed (QALAAI ZANIST JOURNAL, 2022)
The main objective of this study is to determine the significance and the role of theatre as an effective and interesting art of children's literature in planting and developing educational values for children, for the stage of children's age, which the literary text is directed. Descriptive analysis is the method that this paper uses for analyzing the text, and reaching its hypophysis. The paper uses content analysis as its tool for underlining the educational values portrayed in the selected literary text, depending on the criteria of textual analysis in the light of the basic principles that participate in building the dramatical texts. Burhan Qaradaghi’s Rewy Gorany Dalet is the study’s dramatical text. To determine and identify the values that are portrayed in the text in an organized and orderly manner and on a scientific basis, the paper uses Ahmed Ali Kanan’s classification for educational values as its theoretical base and its measurement. The conclusions of the study show that, in this drama “perfection of personality” value set used the most and it is in the highest rate among other value sets, reaching 22.972%. “The national” value set is used the least and it is at the lowest rate, reaching 1.351 percent. It is worth mentioning that among the total educational values used in the play, which are 74 multiple values, the value of “Happiness and play”, which belongs to (entertainment and beauty), is most commonly used, reaching (9.459%).